The Rise of Artificial Intelligence - Wolff, Josh; Gordon, Stephen; Guo, David (Advances in Social Sciences Research Journal, 2018)
Microsoft, together with Cambridge Massachusetts tech startup, Composable Analytics, and Apttus, headquartered in San Mateo delivered an innovative executive level thought leadership event this fall called R.I.S.E. (Robotics, Intelligence, Society, Economy). The challenge was clear - rapid advancements in artificial intelligence (AI), machine learning (ML), robotics, social media, autonomy, image and speech recognition, and other areas of technology will continue to have massive economic and social impact, raising entirely new sets of questions, presenting challenges and new opportunities in every part of society. Key business stakeholders essential to identifying practical, realistic future solutions for these technologies are often not at the table to discuss digital transformation plans or are not aware of the near-term nature of changing technological landscape – what the World Economic Forum calls, a Fourth Industrial Revolution.